A systematic review of randomized controlled trials with herbal medicine on chronic rhinosinusitis. (12th November 2017) - Anushiravani, Majid; Bakhshaee, Mahdi; Taghipour, Ali; Naghedi‐Baghdar, Hamideh; Farshchi, Masoumeh Kaboli; Hoseini, Seyed Saeed; Mehri, Mohammad Reza
Abstract : Chronic rhinosinusitis (CRS) is a common disease with evidence to show that its incidence and prevalence are increasing. Medicinal plants are commonly used to treat CRS. This systematic review aimed to assess the effectiveness and safety of herbal preparations for treatment of the patients with CRS. Cochran, Embase, ISI, PubMed, and Scopus databases were searched until August 1, 2016. Only randomized controlled trials were included. Four randomized controlled trials were included in this systematic review. Various medicinal plants were studied in each article. Inclusion and exclusion criteria, and outcome measures varied among different articles. The results of this trials showed that this special medicinal plants may be effective in the treatment of CRS. No serious reactions were reported during the administration of herbal remedies in the 4 studies. However, trials with a well‐designed approach are needed to study the actual safety and efficacy of herbs in the treatment of CRS.